2021
DOI: 10.1177/15353702211012417
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and matrix metalloproteinases in chronic kidney failure: Modulation by adropin and spexin

Abstract: Chronic kidney disease is a major global public health problem. The peptide hormones adropin and spexin modulate many physiological functions such as energy balance and glucose, lipid and protein metabolism. However, it is unclear whether these peptides may exert effects on renal damage, tissue remodeling, and inflammatory conditions. In view of the limited information, we aimed to investigate the effect of adropin and spexin on matrix metalloproteinase and inflammatory response genes a rat model of adenine-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…The finding of the current study agreed with results previously reported by (43) that found serum Adropin levels were inversely correlated with adverse metabolic parameters including FBS, HbA1C, HOMA-IR and fasting insulin and agreed with (44), as well as (45)showed opposite to current study which reported Serum adropin has negative correlation with HbA1C and fasting insulin and BMI , one possible reason that adropin plays an important role in maintaining metabolic homeostasis, increasing glucose utilization at the expense of fatty acids, improving glucose tolerance, and reducing insulin resistance. The differences between the studies it was highly probable that our observations in T2DM were confounded by variations in disease duration, diabetic complications Metabolically, adropin regulates the activities of the principal pancreatic hormones that control the fate of glucose and fatty acids.…”
Section: Discussionsupporting
confidence: 94%
“…The finding of the current study agreed with results previously reported by (43) that found serum Adropin levels were inversely correlated with adverse metabolic parameters including FBS, HbA1C, HOMA-IR and fasting insulin and agreed with (44), as well as (45)showed opposite to current study which reported Serum adropin has negative correlation with HbA1C and fasting insulin and BMI , one possible reason that adropin plays an important role in maintaining metabolic homeostasis, increasing glucose utilization at the expense of fatty acids, improving glucose tolerance, and reducing insulin resistance. The differences between the studies it was highly probable that our observations in T2DM were confounded by variations in disease duration, diabetic complications Metabolically, adropin regulates the activities of the principal pancreatic hormones that control the fate of glucose and fatty acids.…”
Section: Discussionsupporting
confidence: 94%
“…Also, SPX treatment reduced metalloproteinase-2 (MMP2) levels, which regulates the fibrotic process. 56 These results indicate the protective effect of SPX on renal damage.…”
Section: Kidney Disease and Spxmentioning
confidence: 70%
“…19 Furthermore, SPX treatment decreased IL-33 gene expression in kidney tissue in adenine-induced CRF in rats. 56 In the same experiment, SPX treatment reduced serum IL-5, granulocyte colony-stimulating factor (G-CSF), and IFN-γ levels. 70 Unlike animal studies, there was no observed correlation between SPX and hs-CRP in PCOS patients compared with the control group.…”
Section: Spx Modulates Inflammatory Responsementioning
confidence: 96%
“…Studies have shown that AKT is the key node of PTEN/PI3K/AKT/NF-κB signaling pathway ( Xu J et al, 2021 ; Xu K. et al, 2021 ). In addition, inflammatory response, hormones, and apoptosis are involved in the process of CRF ( Li H et al, 2021 ) ( Wang et al, 2019 ; Yazgan et al, 2021 ). HIF-1 signaling pathway, ErbB signaling pathway, estrogen signaling pathway and other pathways need to be further studied to find new targets for the treatment of CRF.…”
Section: Discussionmentioning
confidence: 99%